Active power optimisation scheduling method for large-scale urban distribution networks with distributed photovoltaics considering the regulating capacity of the main network - Gong, Cheng; Wang, Wei; Zhang, Wenhan; Dong, Nan; Liu, Xuquan; Dong, Yechun; Zhang, Dongying (Frontiers in Energy Research, 2024)
Distributed photovoltaic (PV) access to a large urban distribution network, the active balance brought by it is mainly borne by the main network gas unit, when the scale of distributed PV is too large, the main network can only provide a limited regulation capacity, in this case the distribution network how to carry out active optimal scheduling. This paper proposes an active optimisation scheduling model for a distribution network, considering the regulation capability of the main network. In terms of optimisation objectives, it is proposed that the maximum consumption of distributed PV and the minimum power fluctuation at the main distribution network demarcation point are the main objectives, while the minimum total exchanged power in a cycle at the main distribution demarcation point and the minimum distribution network loss are the secondary objectives; in terms of constraints, it is proposed that the main network's regulation capability is characterised by the main network's gasfired unit climbing constraints. A fast solution method for distribution network active optimisation is designed to formulate the priority control order of adjustable units according to the dispatch economic performance of various types of adjustable resources in the distribution network, which reduces the number of variables involved in the optimisation at each step and improves the optimisation solution speed. Finally, the effectiveness of the above method is verified by arithmetic examples.